2016
DOI: 10.1002/nag.2530
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive model for mechanical and chemo‐mechanical compaction in sedimentary basins and finite element analysis

Abstract: Summary Compaction and associated fluid flow are fundamental processes in sedimentary basin deformation. Purely mechanical compaction originates mainly from pore fluid expulsion and rearrangement of solid particles during burial, while chemo‐mechanical compaction results from Intergranular Pressure‐Solution (IPS) and represents a major mechanism of deformation in sedimentary basins during diagenesis. The aim of the present contribution is to provide a comprehensive 3D framework for constitutive and numerical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Comparison with FE solutions derived from a basin simulator that integrates the effects of large irreversible porosity change on the elastic properties as well as on plastic/viscoplastic hardening laws 36,51 provides ample evidence of the ability of derived semianalytical solutions to relevantly reflect most of local and overall features of the basin deformation. In particular, it has been shown that the simplifying approximations introduced in the resolution formulation affect very little the accuracy of obtained predictions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison with FE solutions derived from a basin simulator that integrates the effects of large irreversible porosity change on the elastic properties as well as on plastic/viscoplastic hardening laws 36,51 provides ample evidence of the ability of derived semianalytical solutions to relevantly reflect most of local and overall features of the basin deformation. In particular, it has been shown that the simplifying approximations introduced in the resolution formulation affect very little the accuracy of obtained predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of pore pressure and geothermal gradient has been assessed through numerical formulations in previous works. 9,41,44,51,52 The sedimentary basin undergoing compaction is modeled as an infinite layer, perpendicular to the e 3 direction and lying on a rigid substratum along the plane x 3 = 0. Neglecting the tectonic activity, the gravitational field g = −ge 3 stands for the only external loading in the compaction process.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations